Methylcobalamin-containing nanofiber sheets have better neuroprotective effects than small intestinal submucosa sheets - Yoshiaki Yoshimura; Toru Iwahashi; Taisuke Kasuya; Toshiki Shimada; Katsuyuki Konishi; Atsushi Kamata; Mai Konishi; Arisa Kazui; Ryoya Shiode; Satoshi Miyamura; Kunihiro Oka; Seiji Okada; et al. (Scientific Reports)
Abstract Postoperative adhesion around nerves sometimes results in sensory and motor dysfunctions. To prevent these disorders, we have developed an electrospun nanofiber sheet incorporating methylcobalamin (MeCbl), an active form of vitamin B12 with anti-inflammatory and neuroregenerative effects. This study aimed to investigate the neuroprotective effects of MeCbl sheets against postoperative adhesion and to compare the effects of MeCbl sheets with those of porcine small intestinal submucosa (SIS) sheets using a rat sciatic nerve adhesion model. Behavioral and electrophysiological analyses showed superior results in the MeCbl sheet group compared with those in the untreated group, all of which were non-inferior to the SIS sheet group. Histological analysis revealed less collagen and inflammatory cell invasion into the nerve parenchyma and a higher number of residual axons and myelination rate in the MeCbl sheet group than in the untreated group. Moreover, the MeCbl sheet group was superior to the SIS sheet group in terms of the myelination rate and decreased number of infiltrating macrophages. Furthermore, the distribution of residual axons by diameter revealed that the MeCbl sheet group had thicker axons than the SIS sheet group. The use of MeCbl sheets may represent a novel approach for preventing secondary nervous system impairment following inflammation.